2018
DOI: 10.1183/23120541.00095-2017
|View full text |Cite
|
Sign up to set email alerts
|

Accumulating physical activity in at least 10-minute bouts predicts better lung function after 3-years in adults with cystic fibrosis

Abstract: In people with cystic fibrosis (CF) reduced fitness and lower levels of physical activity have been associated with poorer prognosis [1] and greater decline in lung function [2]. Despite the health benefits of being physically active [3], in people with CF adherence to exercise programmes is often poor [4], and prescribed exercise training programmes have seldom translated into increased daily physical activity [5].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Whilst the mean duration of exercise sessions in this study was 20 min, below the 30 min of recommended daily PA, 3 it has been shown that accumulation of bouts of as little as 10 min of MVPA could yield long-term benefits in CF. 33 Therefore, use of telehealth could prove to be an integral component of future care and possibly reduce the time required on behalf of clinical teams to engage patients in exercise and PA.…”
Section: Acceptabilitymentioning
confidence: 99%
“…Whilst the mean duration of exercise sessions in this study was 20 min, below the 30 min of recommended daily PA, 3 it has been shown that accumulation of bouts of as little as 10 min of MVPA could yield long-term benefits in CF. 33 Therefore, use of telehealth could prove to be an integral component of future care and possibly reduce the time required on behalf of clinical teams to engage patients in exercise and PA.…”
Section: Acceptabilitymentioning
confidence: 99%
“…Other studies suggest that parental and clinical support, as well as the presence of strong role models, can act as enablers for physical activity in young people, irrespective of whether they are from a CF population [9] or other clinical and non-clinical populations [19, 20]. However, in contrast to the studies that have explored the health benefits of physical activity [21–24], very little is known about what motivates young people with CF to be physically active (or not), what the key enablers and barriers are, and the role of the family. Exploration of these issues could identify opportunities for healthcare providers to enhance sustainable motivation and support young people to become more physically active throughout their lives [25].…”
Section: Introductionmentioning
confidence: 99%
“…Research investigating the relationship between PA and clinical outcomes in CF remains sparse and has mainly focused on individual movement behaviours [45]. Nonetheless, longitudinal investigations have reported a slower decline in FEV 1 with regular PA in paediatric [9] and adult cohorts [7,10]. Amongst these studies, the only one using accelerometery to measure PA showed that accumulating 30 min of MVPA daily is associated with slower FEV 1 decline in adults with CF [10].…”
Section: Discussionmentioning
confidence: 99%
“…PA behaviours are highly collinear [10,11], with each intensity representing a proportion of the total waking time [12]. Thus, the amount of time allocated to one behaviour will directly affect the time available for all others [13].…”
Section: Introductionmentioning
confidence: 99%